1998
DOI: 10.1073/pnas.95.17.10015
|View full text |Cite
|
Sign up to set email alerts
|

Mutation frequency declines during spermatogenesis in young mice but increases in old mice

Abstract: Five percent of live-born human offspring will have a genetic disorder. Of these, 20% are because of germ-line de novo mutations. Several genetic diseases, such as neurofibromatosis and Duchenne muscular dystrophy, are associated with a high percentage of de novo germ-line mutations. Until recently, a direct analysis of spontaneous mutation frequencies in mammalian germ cells has been prevented by technical limitations. We have measured spontaneous mutation frequencies in a lacI transgene by using enriched pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
121
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 26 publications
19
121
0
3
Order By: Relevance
“…Consistent with previous results [27], the spontaneous mutant frequency in type A spermatogonia is significantly greater than that in the later spermatogenic cell types and the reduction in mutant frequency takes place between type A spermatogonia and type B spermatogonia (Table 1). However, after IR treatment the return to the low spontaneous mutant frequency occurred later in spermatogenesis (Figures 2-5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous results [27], the spontaneous mutant frequency in type A spermatogonia is significantly greater than that in the later spermatogenic cell types and the reduction in mutant frequency takes place between type A spermatogonia and type B spermatogonia (Table 1). However, after IR treatment the return to the low spontaneous mutant frequency occurred later in spermatogenesis (Figures 2-5).…”
Section: Discussionsupporting
confidence: 92%
“…However, after IR treatment the return to the low spontaneous mutant frequency occurred later in spermatogenesis (Figures 2-5). Together with our previous study [27], it is clearly shown that spontaneous and IR-induced mutant frequencies can be reduced during spermatogenesis. The mechanism by which mutant frequency is reduced is not yet identified.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The phenomenon described here may be part of a general selection mechanism against mutations. Mutation frequency declines during spermatogenic differentiation [Walter et al, 1998;Xu et al, 2008] suggesting that mechanisms have evolved to prevent germ cell transmission of genetic damage. Mutations induced by irradiation of A/B spermatogonia were shown to decline with cell differentiation, probably because of delayed apoptosis [Xu et al, 2008[Xu et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was shown that the risk of childhood acute lymphoblastic leukemia was significantly higher among children of older mothers and fathers, and significant trends with increasing mothers's and fathers' ages were found. It is worthy nothing that spermatogenic cells from old mice have significantly increased mutation frequencies compared with spermatogenic cells from young or middle-aged mice [73]. New dominant mutation rise exponentially with parental age but not matergnal age in humans [74].…”
Section: Aging and Multi-stage Carcinogenesismentioning
confidence: 99%